Porewater δ13 CDOC indicates variable extent of degradation in different talik layers of coastal Alaskan thermokarst lakes - Meisel, Ove H.; Dean, Joshua F.; Vonk, Jorien E.; Wacker, Lukas; Reichart, Gert Jan; Dolman, Han (Biogeosciences, 2021)
Thermokarst lakes play an important role in permafrost environments by warming and insulating the underlying permafrost. As a result, thaw bulbs of unfrozen ground (taliks) are formed. Since these taliks remain perennially thawed, they are zones of increased degradation where microbial activity and geochemical processes can lead to increased greenhouse gas emissions from thermokarst lakes. It is not well understood though to what extent the organic carbon (OC) in different talik layers below thermokarst lakes is affected by degradation. Here, we present two transects of short sediment cores from two thermokarst lakes on the Arctic Coastal Plain of Alaska. Based on their physiochemical properties, two main talik layers were identified. A "lake sediment"is identified at the top with low density, sand, and silicon content but high porosity. Underneath, a "taberite"(former permafrost soil) of high sediment density and rich in sand but with lower porosity is identified. Loss on ignition (LOI) measurements show that the organic matter (OM) content in the lake sediment of 28±3 wt% (1σ, n = 23) is considerably higher than in the underlying taberite soil with 8±6 wt% (1σ, n = 35), but dissolved organic carbon (DOC) leaches from both layers in high concentrations: 40±14 mg L-1 (1σ, n = 22) and 60±14 mg L-1 (1σ, n = 20). Stable carbon isotope analysis of the porewater DOC (δ13CDOC) showed a relatively wide range of values from -30.74‰ to -27.11‰ with a mean of -28.57±0.92‰(1σ, n = 21) in the lake sediment, compared to a relatively narrow range of -27.58‰to -26.76‰ with a mean of -27.59±0.83‰(1σ, n = 21) in the taberite soil (one outlier at -30.74 ‰). The opposite was observed in the soil organic carbon (SOC), with a narrow δ13CSOC range from -29.15‰ to -27.72‰ in the lake sediment (-28.56±0.36 ‰, 1σ, n = 23) in comparison to a wider δ13CSOC range from -27.72‰ to -25.55‰ in the underlying taberite soil (-26.84±0.81 ‰, 1σ, n = 21). The wider range of porewater δ13CDOC values in the lake sediment compared to the taberite ...